Unique Raoultella species isolated from petroleum contaminated soil degrades polystyrene and polyethylene - Yuan, Yingbo; Liu, Pan; Zheng, Yi; Li, Qingbin; Bian, Junling; Liang, Quanfeng; Su, Tianyuan; Dian, Longyang; Qi, Qingsheng (Ecotoxicology and environmental safety, 2023)
Polyolefin plastics, such as polyethylene (PE) and polystyrene (PS), are the most widely used synthetic plastics in our daily life. However, the chemical structure of polyolefin plastics is composed of carbon-carbon (C-C) bonds, which is extremely stable and makes polyolefin plastics recalcitrant to degradation. The growing accumulation of plastic waste has caused serious environmental pollution and has become a global environmental concern. In this study, we isolated a unique Raoultella sp. DY2415 strain from petroleum-contaminated soil that can degrade PE and PS film. After 60 d of incubation with strain DY2415, the weight of the UV-irradiated PE (UVPE) film and PS film decreased by 8% and 2%, respectively. Apparent microbial colonization and holes on the surface of the films were observed by scanning electron microscopy (SEM). Furthermore, the Fourier transform infrared spectrometer (FTIR) results showed that new oxygen-containing functional groups such as -OH and -CO were introduced into the polyolefin molecular structure. Potential enzymes that may be involved in the biodegradation of polyolefin plastics were analyzed. These results demonstrate that Raoultella sp. DY2415 has the ability to degrade polyolefin plastics and provide a basis for further investigating the biodegradation mechanism. [Display omitted] •Raoultella sp. DY2415 is a unique polystyrene and polyethylene degrading strain.•The morphological and chemical structure changes were observed for plastic films treated with Raoultella sp. DY2415.•UV-irradiated polyethylene exhibited 8% weight loss after 60 d incubation with Raoultella sp. DY2415.•Several candidate enzymes may be relevant to polyolefin plastic degradation.